2018
DOI: 10.32011/txjsci_70_1_article6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiant Catalytic Ionization in Reducing Escherichia Coli, Listeria Innocua and Salmonella Typhimurium on Representative Food Contact Surfaces

Abstract: Escherichia coli, Listeria spp. and Salmonella typhimurium are common food pathogens and responsible for frequent and widespread outbreaks of foodborne illness annually. This study examines the potential of radiant catalytic ionization (RCI) as a food decontamination technology through its reduction of inoculations of these bacteria on representative food items (apples, cantaloupes, and spinach). RCI exposure resulted in ≥99% reduction in the recovery of these bacteria within a 90-min exposure, with two except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…According to Ortega et al [25], the reduction of different microorganisms, including foodborne pathogens, on stainless steel surfaces subjected to 24 h of RCI treatment reached at least 90%. RCI efficacy against Salmonella on food contact surfaces and animal food products was also confirmed [28,40]. The present research showed the inhibition of C. jejuni, L. monocytogenes, and S. Enteritidis strains on a glass surface after RCI treatment.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…According to Ortega et al [25], the reduction of different microorganisms, including foodborne pathogens, on stainless steel surfaces subjected to 24 h of RCI treatment reached at least 90%. RCI efficacy against Salmonella on food contact surfaces and animal food products was also confirmed [28,40]. The present research showed the inhibition of C. jejuni, L. monocytogenes, and S. Enteritidis strains on a glass surface after RCI treatment.…”
Section: Discussionsupporting
confidence: 74%
“…The antimicrobial efficiency of RCI is attributed to the cell damaging effect of oxidative gases, including ozone and peroxide, generated by the RCI cell [25,28]. The inhibition of pathogenic microorganisms on various surfaces was confirmed by our previous studies [8,26,27].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The photocatalysis process with UV radiation and TiO 2 as a catalyst as a method of inactivation of microorganisms (Lactobacillus acidophilus, Saccharomyces cerevisiae cerevisiae and Escherichia coli) in water was first used by Matsunaga et al (1988). The effectiveness of photocatalysis for water sterilization has been demonstrated by many researchers (Saito et al 1992;Wei et al 1994;Sunada et al 1998;Maness et al 1999;Marug an et al 2008). The results of these studies were satisfactory as they were characterized by a high level of bacterial inactivation.…”
Section: Radiant Catalytic Ionization-principle Of Operation and Cons...mentioning
confidence: 99%